What the Death Star can tell us about ergonomics methods. (3rd July 2016) - Walker, Guy; Salmon, Paul; Bedinger, Melissa; Stanton, Neville
ABSTRACT: Imagine having to identify a critical flaw in a highly complex planetoid-sized orbital battle station under extreme time pressure, and with no clear idea at the outset where the vulnerability will lie? This was the challenge faced by the Rebel Alliance in the film Star Wars. One of the belligerents, the Imperial Empire, considered it highly unlikely a weakness would be found even if the other combatant were in possession of a full technical readout of the station. How could it be done? The first option presented in this paper is to employ traditional error identification methods of the sort contemporaneous with the film's release in 1977 and still in widespread use today. The findings show the limitations of this deterministic world-view because the method selected did not predict the actual vulnerability exploited. The second option is to use a systems-based method to model the Death Star's functional constraints and affordances and use this to assess the system's resilience. This method did detect the film ending, and several others. What began as an amusing aside has turned into a highly effective means to communicate across disciplines and enhance ergonomic teaching and learning. It also provides a compelling narrative around the use of reductionist methods for systems problems, and some wider implications for ergonomic method selection in more earth-bound settings.